Relationship between Sleep Quality and Blood Sugar Levels in Patients with Type II Diabetes Mellitus - Salsa, Salsa Febriyanti; Kurniasari, Fitri Anita, Septi (Java Nursing Journal, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a major global health concern with increasing prevalence, significantly impacting quality of life and health systems. Sleep disturbances are commonly found in T2DM patients and may impair glycemic control through metabolic and hormonal dysregulation. Purpose: This study aimed to analyze the association between sleep quality and blood sugar levels in patients with type II Diabetes Mellitus at Adventist Hospital Bandar Lampung, Indonesia. Methods: A quantitative cross-sectional design was employed involving 86 T2DM patients selected from a population of 949 using purposive sampling. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), while blood sugar levels were retrieved from patient medical records. Data collection was conducted between January 10 and February 10, 2025. The chi-square test was used for statistical analysis, with a significance level set at p ≤ 0.05. Ethical approval was obtained from the Health Research Ethics Committee of Mitra Indonesia University. Results: Most respondents (75.6%) had poor sleep quality and uncontrolled blood sugar levels. Statistical analysis revealed a significant association between sleep quality and blood sugar control (p = 0.000). Specifically, 76.2% of patients with good sleep quality had controlled blood sugar, while 92.3% of those with poor sleep quality had uncontrolled levels. Conclusion: Sleep quality is significantly associated with glycemic control in patients with type II Diabetes Mellitus. These findings highlight the need to integrate sleep assessments into routine diabetes care. Enhancing patient and healthcare provider awareness regarding the role of sleep may contribute to more effective T2DM management